Persuasive Communication Between Wedding Photographers and Consumers During Covid-19 in Completing Work Contracts - Muhammad Riandika Pratama (Talenta Publisher, 2024)
The impact of the Covid-19 virus that has struck Indonesia is also felt by photographers, especially in the context of weddings. Wedding events during the Covid-19 pandemic significantly affect photographers in providing good services to customers due to the involvement of two large families. Photographers must have strategies to attract customers. One possible strategy that photographers may use in this regard is employing persuasive communication. Therefore, this research aims to analyze the processes and obstacles of verbal and non-verbal persuasive communication between photographers and customers in completing work contracts. This study is qualitative with a constructivist paradigm. The results indicate that the persuasive communication employed by photographers provides a sense of safety and comfort to customers. Obstacles such as time delays pose challenges for photographers